Vermicompost as a Potential Organic Source and Partial Substitute for Inorganic fertilizers in Sweet potato (Ipomoea batatas (L.) Lam.) - Suresh Kumar S N (Department Of Soil Science And Agricultural Chemistry,College Of Agriculture, 1998)
An investigation entitled "Verrnicompost as a potential organic source and partial substitute for inorganic fertilizers in sweet potato (Ipomoea batatus (L) Lam)" was carried out at the Instructional Farm, College of Agriculture, Vellayani during the period December 1995 to April 1996. The main objectives of the study were to study the efficiency of vermicompost as an organic manure, the extent to which inorganic fertilizers can be substituted when vermicompost was used as an organic source and the feasibility of